Journal of Ecology and Environment
The aim of the Journal of Ecology and Environment is to provide a forum for the ecologist to address and evaluate ecological issues relating to processes and structures at different integration levels (individuals, populations, communities, ecosystems and the landscape). The journal bridges fundamental ecology and environmental ecology and spans the boundaries of spatial and temporal scale, discipline and perspective.